Blossom-end rot in tomato - Pereira, J. R.; Fernandes, C. S.; Cordeiro, G. G. (Pesquisa Agropecuaria Brasileira, 2014)
The main objective was to study the effects of liming and foliar application of CaCl2 0.4% and CaSO4 0.6% on the incidence of blossom-end rot of tomato (Lycopersicum esculentum Mill.) var. Rossol. Liming was not effective in controlling this physiological disorder in the tomato fruit, even though it has contributed to reduce the incidence in about 25%. The treatments with CaCl2 0.4% and CaSO4 0.6% showed no effect in decreasing the rate of blossom-end rot. Liming, however increased the yield in 18%.